The Problems of Teaching Reading with Online Learning - Muflihah Muflihah; Arif Sukirno (English Education : English Journal for Teaching and Learning, 2021)
COVID-19 pandemic change the world, especially for the education. Nearly 1.6 billion learners in the world affected by this phenomenon. So, Indonesia’s government must issue the rule of online learning for the sake of everyone’s safety. It also affects the English language learning as well, especially reading. This study is about the problems of teaching reading with online learning especially in IAIN Purwokerto, Central Java, mainly with the use of Zoom and Google Meet. The author of this article is interested and wants to know very much about it. So, he conducted the research to find the answer about it. The research used qualitative approach, and the data collection technique is interview and literature review of the journals and books. Some results are found, such as the limitation of technologies, students that don’t activate the camera during learning, the teacher can’t observe the students’ respond to the material that have been prepared, and other problems that will be explained further in this article. The author also hope that this article can help making better future of the education, especially for the online learning.